Utilizatin of Information Systems to Increase Learning Motivation Using Sway at Nuurul Muttaqiin Vocational School - Umamah, Ai; Bariah, Siti Husnul; Faujuah, Siti Husnul (Fakultas Kewirausahaan Universitas Garut, 2024)
This community service with the title Utilization of information systems to increase learning motivation using Microsoft SWAY for students of SMK Nuurul Muttaqiin Cisurupan Garut. PKM is carried out at SMK Nuurul Muttaqiin Cisurupan Garut. The objectives include: 1) to increase learning motivation, 2) utilization of application-based information technology, the methods used are lectures, cooperation, and mentoring. In this service, the results that have been achieved have received a good response to the implementation of PKM, which is indicated by the interest in learning to use the sway application.